Goods trade liberalization under the ASEAN Economic Community effects on the Philippine economy - Clarete, Ramon L.; Tuaño, Philip Arnold P. (2015)
The economy-wide effects of the asean Free Trade Area (afta) on the Philippine economy are computed using the Global Trade Analysis Project (gtap) model of the world economy. Of the 40 industries representing the Philippine economy that were simulated to assess the impacts of afta on sectoral output, 24 industries declined. However, the order of magnitudes of the percentage declines is low, except for rice, whose output decreased by about 4.5 percent.

Notwithstanding the contraction of production in the majority of industries, the country comes out a net gainer in aggregate output by around 1.4 percent in total gross domestic product. This implies that, overall, the Philippines is slightly better off with the preferential trade liberalization, with an equivalent variation gain of us$237.4 million.

Considerable movement of workers across industries is observed. Reductions in skilled worker employment resulted in 31 industries, and 35 industries do the same in the case of unskilled labor. There is no change in unemployment due to the fact that the empirical model assumes full employment of productive factors. Given the fact that there is a change in employment patterns during trade liberalization episodes, it is important to assess the empirical relationship between trade liberalization and unemployment which remains difficult to pin down.

The empirical literature in developing countries shows that the employment response of trade reforms is dependent on infrastructure, trade facilitation measures, and other policies. Therefore, policies related to providing information and new market opportunities, organizing value chains, facilitating coordinated investments along the chain, clustering of related small and medium enterprises to boost external economies, and providing information to employers and workers of job opportunities, including training, are important.
Keywords: Free trade; ASEAN Countries -- Economic relations